Determinants of Access to Decent Housing for Low Income Communities (LICs) in Indonesia with Housing Assistance as a Policy Instrument - Nabilla, Afifah; Prasetyia, Ferry; Kurnia Suci, Apriani (Journal of Development Economic and Social Studies, 2026)
Housing assistance programs play an important role for Low Income Communities (LICs) in gaining access to decent housing. Based on the literature, research has generally been limited to static analysis and descriptive evaluation of programs, so that the results obtained do not fully describe the dynamics over time and differences in regional characteristics comprehensively. This study aims to analyze the role of BSPS for LICs and the factors that influence access to decent housing. The data used from 34 provinces in Indonesia in 2015 to 2023. The data was analyzed using two way fixed effects estimation, and System GMM as robustness checks. The analysis shows that the distribution of BSPS units cannot improve access to decent housing. The main objective of the BSPS program in reaching LICs has not fully achieved. But the non food poverty line, provincial minimum wage, human development index, and realization of government subsidies funds are factors that correlate with access to decent housing.